2001
DOI: 10.1046/j.1537-2995.2001.41030365.x
|View full text |Cite
|
Sign up to set email alerts
|

Donor‐derived alloantibodies and passenger lymphocyte syndrome in two of four patients who received different organs from the same donor

Abstract: The amount of cotransplanted lymphoid tissue may correlate with the extent of peripheral lymphoid microchimerism and the antibody-formation capacity in solid organ transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 20 publications
1
42
0
2
Order By: Relevance
“…Studies have shown the importance of humoral immune reaction to these donor-specific HLA-related antigens (14). Specifically, the presence of pretransplantation PRA is associated with an adverse post-transplantation outcome compared with those patients in whom the PRA test is low or negative (15,16). Among the adverse post transplant events are acute cellular rejection, decreased longterm graft survival, increased mortality and accelerated coronary heart disease (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the importance of humoral immune reaction to these donor-specific HLA-related antigens (14). Specifically, the presence of pretransplantation PRA is associated with an adverse post-transplantation outcome compared with those patients in whom the PRA test is low or negative (15,16). Among the adverse post transplant events are acute cellular rejection, decreased longterm graft survival, increased mortality and accelerated coronary heart disease (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with graftversus-host disease after liver, lung, or intestinal transplantation donor T cell chimerism is well described (12), but is very rare after kidney or heart transplantation. Donor B cell microchimerism has, however, been detected in patients who developed red blood cell alloantibodies following liver and kidney-pancreas transplantation (16). In the two recipients described here, the novel suggestion that the development of posttransplant de novo HLA-specific alloantibodies was caused by the adoptive transfer of donor alloreactive passenger B cells/plasma cells within the kidney was not initially apparent and we did not therefore test for peripheral blood donor B cell chimerism.…”
mentioning
confidence: 75%
“…None of the recipients had irregular RBC alloantibodies at the time of transplantation, but anti-K and anti-Fy(a) became detectable in the liver recipient and the pancreas-kidney recipient. As discussed above, the amount of cotransplanted lymphoid tissue may correlate with the extent of peripheral lymphoid microchimerism and alloimmunization in solid-organ transplantation as well as in allogeneic SCT [65,85,87].…”
Section: Minor Abo Incompatibilitymentioning
confidence: 99%
“…Because transfusion of ABO-incompatible blood already below 100 ml can result in acute, severe transfusion reactions, it may be technically impossible to reduce residual circulating recipient RBCs to clinically insignificant levels [7]. Seltsam et al [87] reported of RBC alloimmunization by donor-derived lymphocytes after solid-organ transplantation in 2 of 4 patients who received different organs from an immunized donor. Lymphoid microchimerism in the blood of the recipients was detected by flow cytometry and PCR.…”
Section: Minor Abo Incompatibilitymentioning
confidence: 99%